The Effectiveness of Transactional Analysis Counseling to Increase Self Esteem - Sundah, Ariantje J.A (International Journal of Scientific Research and Management (IJSRM), 2018)
The research aims to describe and test the effectiveness of transactional analysis counseling to increase students self-esteem. The subjects of this studi  at  Junior High School at Airmadidi, North Minahasa Regency,North Sulawesi-Indonesia. A low self-esteem based measurement instruments on self-esteem. Numerical data were analyzed using two independent-sample test Mann Whitney-U test. While verbal data using method of conversation analysis through recording counseling (verbatim). The result of analysis from the experimental group shows that transactional counseling can to increase to self-esteem students of junior high school. Research recommendations are: (1) school counselors need to receive transactional counseling counseling training especially to improve the low self-esteem of learners, (2) Principals, it is advisable to provide adequate counseling services phenomenon in schools, (3) Transactional analysis can be used to help improve other psychological aspects such as self-eficacy. Transactional analysis counseling proved effective enough to improve self-esteem students with low self-esteem. Transactional analysis counseling is effective enough to improve self-esteem in all three aspects striving, self-evaluation, and learning. Specifically, the aspect of self-evaluation has the ability to increase self-esteem.